A cognitive processing therapy-based treatment program for veterans diagnosed with co-occurring posttraumatic stress disorder and substance use disorder: The relationship between trauma-related cognitions and outcomes of a 6-week treatment program. (October 2018) - Peck, Kelly R.; Coffey, Scott F.; McGuire, Adam P.; Voluse, Andrew C.; Connolly, Kevin M.
Highlights: Prior to treatment, dysfunctional trauma-related cognitions were associated with PTSD and depressive symptoms, and trauma-cued craving. Following treatment dysfunctional trauma-related cognitions, PTSD and depressive symptoms, and trauma-cued craving decreased. Decreases in dysfunctional trauma-related cognitions mediated the corresponding improvement in treatment outcomes upon program completion. Reductions in maladaptive trauma-related cognitions appear to play an important role in recovery from PTSD. CPT-based interventions that modify trauma-related cognitions can lead to desirable outcomes among veterans with co-occurring PTSD and SUD. Abstract: Dysfunctional trauma-related cognitions are important in the emergence and maintenance of posttraumatic stress disorder (PTSD) and the modification of such cognitions is a proposed mechanism of trauma treatment. However, the authors are not aware of any research examining trauma-related cognitions as a treatment mechanism in a sample of individuals with comorbid PTSD and substance use disorder (SUD). Accordingly, the present study sought to address this gap in the literature and examined the relationship between trauma-related cognitions and treatment outcomes within a sample of seventy-two veterans diagnosed with PTSD and SUD. Veterans completed a 6-week day CPT-based treatment program that included cognitive processing therapy as a central component. Measures of trauma-related cognitions, PTSD symptoms, depressive symptoms, and trauma-cued substance craving were completed at pre- and post-treatment. As expected, trauma-related cognitions were associated with several PTSD-related variables prior to treatment. Furthermore, results of a within-subjects mediational analysis indicated that maladaptive trauma-related cognitions decreased during the treatment program and accounted for a significant portion of the variance in the reduction of PTSD and depressive symptoms at post-treatment. This study provides support for the position that attempts to modify dysfunctional trauma-related cognitions among veterans with co-occurring PTSD and SUD can lead to desirable treatment outcomes.